2010
DOI: 10.1021/jf100233y
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Gallic Acid and Its Esters on 2,2′-Azobis(2-amidinopropane)hydrochloride (AAPH)-Induced Hemolysis and Depletion of Intracellular Glutathione in Erythrocytes

Abstract: The protective effect of gallic acid and its esters, methyl, propyl, and lauryl gallate, against 2,2'-azobis(2-amidinopropane)hydrochloride (AAPH)-induced hemolysis and depletion of intracellular glutathione (GSH) in erythrocytes was studied. The inhibition of hemolysis was dose-dependent, and the esters were significantly more effective than gallic acid. Gallic acid and its esters were compared with regard to their reactivity to free radicals, using the DPPH and AAPH/pyranine free-cell assays, and no signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 42 publications
1
37
0
Order By: Relevance
“…The crude products were purified over a silica gel column eluted with mixtures of hexanes and EtOAc, furnishing alkyl gallates (compounds 2 to 16) ( Table 1). The molecular structures of these compounds were established by 1 H and 13 C nuclear magnetic resonance (NMR) spectral analysis (16,17).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The crude products were purified over a silica gel column eluted with mixtures of hexanes and EtOAc, furnishing alkyl gallates (compounds 2 to 16) ( Table 1). The molecular structures of these compounds were established by 1 H and 13 C nuclear magnetic resonance (NMR) spectral analysis (16,17).…”
Section: Methodsmentioning
confidence: 99%
“…Synthetic esters of gallic acid were prepared as described previously, with minor modifications (16,17). A 3.0-ml solution of N,N=-dicyclohexylcarbodiimide (DCC) (1.0 mmol) in dried p-dioxane was added to a cooled (5°C) solution of 0.2 mmol gallic acid (Sigma) (compound 1) (Table 1) and 20 mmol alkyl alcohol in 6.0 ml of dried p-dioxane.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hsieh et al (28) found that, under in vitro conditions, gallic acid protected human erythrocytes from oxidative damage. In contradiction to this fi nding, Ximenes et al (29) suggested that gallic acid is prooxidative in cellular systems and could exacerbate the drug-induced prooxidative damage in human erythrocytes. The prooxidative effect of gallic acid at the molecular level (30) and oxidative-based induction of cell death in cancer cells (31,32) have also been documented.…”
Section: Resultsmentioning
confidence: 87%
“…However, its effect to inhibit inflammatory activity still could not be omitted. It was previously reported that gallic acid in TC to possessed anti-inflammatory (Ximenes et al, 2010). Unfortunately, this study did not investigate about the possible active ingredients and the precise underlying mechanisms of this extract could attenuate memory impairment; this is planned in future studies.…”
Section: Discussionmentioning
confidence: 99%